Canine atopic dermatitis datasets - Tengvall, Katarina (Uppsala University, 2022)
The datasets consists of genotype data from dogs in plink format.

ATOPYK2 plink files contains genotype data from five dog breeds with and without atopic dermatitis. The ATOPYK2 datafiles were used for imputation. These are pre-QC:ed with the following plink settings --maf 0.001 --geno 0.05 --mind 0.05

#We recommend a second qc before doing the imputation. The imputation was then run per chromosome so for redoing the imputation, as was done in the publication to which this data is connected, use the following plink code:

plink --bfile ATOPYK2 --chr $chrN --make-bed --dog --allow-no-sex --keep-allele-order --maf 0.001 --geno 0.2 --out 'ATOPYK.chr'$chrN

#The final datasets after imputation are datasets split breed wise and in plink format. These sets are QC:ed, and relatedness filtered. The "covar"-file includes fixed effects, these are different between depending on what covariates were significantly affecting the trait (atopic dermatitis) in each breed. These datasets are named GR (golden retriever), LR (labrador retriever), GSD (german shepherd) and WHWT (west highland white terrier). (Boxers are in the ATOPYK2 files but not used for final analyses, hence no breed specific datafile for boxer are included).
Keywords: Gene mapping; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik